KAMPANYE SADAR LINGKUNGAN DI AREA WISATA PANTAI ARMY DOCK KABUPATEN PULAU MOROTAI - Kismanto Koroy; Nurfani Nurfani (Jurnal Pasca Dharma Pengabdian Masyarakat, 2020)
The Army Dock is a historic beach resort, where during the second world war this place served as a port for warships. Visitor activities in the Army Dock beach tourism location which varies greatly from swimming, enjoying the scenery, beach sports, sunbathing and other activities, will also have an impact on the carrying capacity of the environment. One of the environmental impacts which is a problem is the lack of awareness of visitors who still dispose of their trash improperly . The aim of this activity is to conduct an environmentally conscious campaign through beach cleaning and billboard placement so that visitors for the sake of sustainability in the future.The method used in community service is counseling and activities accompanied by the creation and installation of invitation boards (environmental awareness campaigns). In this activity students, lecturers and visitors also participated. Cleaning the beach is done by going along the beach area of the tourist location by collecting rubbish . The involvement of visitors in beach cleaning activities and the installation of invitation boards, has indirectly shaped psychological behavior. This can be seen from their enthusiasm and participation to be able to join and assist the team in carrying out these activities . With the response from visitors and the local community canemphasizes the importance of preserving and maintaining the cleanliness of our environment, especially the coastal and marine environment so that it can attract tourists to visit the Army Dock beach.